1990
DOI: 10.1007/bf02578636
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects and results of percutaneous transluminal angioplasty in Brescia-Cimino dialysis fistulas

Abstract: Our experience with percutaneous transluminal angioplasty for treatment of stenoses and occlusions in surgically created arteriovenous fistulas (Brescia-Cimino) is reported. Methodological aspects are emphasized. Forty-nine PTAs were performed in 36 patients, in 3 combined with the use of a vascular metallic endoprosthesis (Wallstent). The initial success rates for stenoses and occlusions were 91% and 77%, respectively. Long stenoses and occlusions (greater than 4 cm) showed significantly worse initial results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Our PTA technique was based on standard methods reported previously [4]. Patients received 1% lidocaine local anesthesia prior to the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our PTA technique was based on standard methods reported previously [4]. Patients received 1% lidocaine local anesthesia prior to the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Many investigators have reported that Brescia-Cimino arteriovenous fistulas have several advantages to polytetrafluoroethylene grafts, especially for a longer lifetime [1,2,3,4,5,8,9,10]. Despite the increased reliability, however, Brescia-Cimino arteriovenous fistulas often require radiological or surgical interventions frequently to maintain their function [1,2,3,4,5,8,9,10].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations